FACTORS INFLUENCING PREGNANT WOMEN'S COMPLIANCE IN CONSUMING IRON (Fe) TABLETS IN THE WORKING AREA OF THE INGIN JAYA PUSKESMAS, ACEH BESAR DISTRICT, 2023 - Gadis Halizasia; Nelva Riza; Reka Julia Utama (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Pregnant women usually complain of fatigue, headaches, shortness of breath, pale faces, and various other complaints. All these complaints are an indication that the pregnant woman is suffering at the Ingin Jaya Health Center, Aceh Besar Regency. This study aimed to determine the relationship between factors that influence pregnant women's compliance with iron tablets and their relationship to the incidence of anemia at the Ingin Jaya Community Health Center. This research method is analytical with a Cross-Sectional study research design. The sampling technique was purposive sampling with a sample size of 42 people—data analysis using Chi-Square. The results showed that from 42 samples, 54.8% of pregnant women were categorized as non[1]compliant, 66.7% had low knowledge, 42.9% had negative attitudes, 100% had good health services and 59.5% lacked family support. All research variables have a significant relationship with knowledge, attitudes, family support, and compliance with the incidence of anemia. It is recommended that pregnant women adhere to taking iron tablets during pregnancy and know the consequences if they are not consumed properly. Iron tablets that have been given by health workers.